Modification of Gambier extracs as green inhibitor of calcium carbonate (CaCO3) scale formation. (August 2017) - Suharso,; Reno, Tiand; Endaryanto, Teguh; Buhani,
Highlights: The problems of Gambier extracts as inhibitor are easily damaged and cannot be stored for long time. The addition of benzoic and citric acid into the Gambier extract lead to significant quality of this mixture. The inhibition efficiency of the mixture in inhibiting CaCO3 scale formation is around 12–92%. The addition of the mixture changes the morphology and crystal size of the CaCO3 crystals. Abstract: The addition of the Gambier extract ( Uncaria gambier Roxb leaves) modification (Gambier:benzoic acid:citric acid/2:1:2) as a green inhibitor on the formation of CaCO3 scale at various concentrations was carried out using a seeded experiment method. The experiments were performed with observing the precipitation change of the CaCO3 crystals growth obtained. In order to prove the efficiency of the inhibitor in inhibiting the formation of the CaCO3 crystals, the changes of the crystal morphology were investigated by scanning electron microscopy (SEM) and the changes of the crystal size distribution were analyzed by particle size analyzer (PSA). The research results showed that the Gambier extract modification was able to inhibit the formation of the CaCO3 scale indicated with the morphology change of the CaCO3 crytals and smaller crystal size distribution after the addition of this inhibitor.